PENINGKATAN KEMAMPUAN MENULIS ESAI MELALUI PROBLEM BASED LEARNING BERBANTUAN MEDIA AI QUANDARY PADA PEMBELAJARAN SOSIOLOGI - Siti Nofiati (Badan Perencanaan Pembangunan Penelitian dan Pengembangan Daerah Kabupaten Cilacap, 2024)
This study aims to improve essay writing skills through the application of PBL assisted by the AI Quandary media in sociology lessons for tenth-grade students at SMA Islam Al Azhar 35 Cilacap. This Classroom Action Research (CAR) was conducted in two cycles, with each cycle consisting of planning, implementation, observation, and reflection stages. The instruments used in this study included observation sheets, essay writing skill assessment sheets, and documentation. The results showed that the implementation of Problem-Based Learning assisted by AI Quandary significantly improved students' essay writing skills. Overall, the application of Problem Based Learning, supported by the interactive AI Quandary media, proved to be effective in enhancing students' essay writing abilities. The use of AI Quandary helped students better understand the issues and develop stronger arguments. This study suggests that Problem Based Learning with the support of technology like AI Quandary should be more widely implemented in sociology learning.